Colonialism, African Women, and Human Rights in Nervous Conditions by Tsitsi Dangarembga - De Villiers, Isolde (University of Pretoria, 2017)
The Universal Declaration of Human Rights (UDHR) in 1960, with its emphasis on protection and promotion of human rights, signalled a new path for the likely achievement of equality, democracy, and world peace. .However, challenges still exist for African women despite the promise that human rights hold. My curiosity is why this seemingly perfect solution to world problems has not worked and is not working. The study, firstly, aims at exploring the effect of colonialism on African women's lives in Tsitsi Dangarembga's Nervous Conditions and how it is still evident in postcolonial present. Secondly, it examines how the text challenges the classic bildungsroman and how this aids as a test to the celebratory human rights story of today. Finally, it investigates the relationship between colonialism and human rights and the role religion and patriarchy plays. In pursuit of the central research problem, I use Law and Literature in an attempt to understand the inadequacies of Law. Law and Literature allow for a detailed literary analysis of Law and legal systems. Nervous Conditions provides realistic scenarios of the continued oppression of African women in African society. While the celebratory human rights story is triumphant and successful, Dangarembga's subversion of the classic bildungsroman points to the oppressive condition of African women and the inadequacy of human rights. African women in Dangarembga's stories have no successful end as the norm for a classical bildungsroman plot. Colonialism and its legacy, patriarchy and religion still have a hold on African women, rendering promised celebratory human rights narrative unattainable. Literature has the opportunity to expose African women's issues not addressed by Law. . In a bid to show the effects of colonialism and its continual hold in Africa and specifically for African women, I employ the postcolonial theory that enables me to show a society divided along the lines of gender, race, and material possessions. The postcolonial theory also reflects the Eurocentric ideology that drives the colonial mind-set and its continual existence. I examine Nervous Conditions using Critical Discourse Analysis (CDA), which allows for dissection of the text through searching critically for incidents that display power, control, and authority along gender lines, places, and positions within the society. I also critically look at Dangarembga's language usage that reflects those power differences and structures in Nervous Conditions. As reflected in Nervous Conditions, struggles for African women continue even in post- independent Africa. The presence of human rights remains a promise for many African women.